2017
DOI: 10.1186/s12884-016-1187-2
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Asian ethnicity and obstetric intrapartum intervention: a retrospective cohort study

Abstract: BackgroundMaternal ethnicity is a recognized risk factor for stillbirth, such that South Asian women have higher rates than their Caucasian counterparts. However, whether maternal ethnicity is a risk factor for intrapartum outcomes is less clear. The aim of this study is to explore associations between maternal country of birth, operative vaginal delivery and emergency cesarean section, and to identify possible mechanisms underlying any such associations.MethodsWe performed a retrospective cohort study of sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…One team in Victoria demonstrated that, compared with Australian‐born women, East African maternal region of birth was associated with increased risk of perinatal death and some adverse perinatal outcomes 14 . Other Australian studies found an association between maternal region of birth and risk of obstetric intervention during birth 15,16 . Finally, another team in Victoria reported that late preterm births to South Asian‐born women were less likely to be admitted to the nursery and had better respiratory outcomes than those born to Australian/New Zealand‐born women 17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One team in Victoria demonstrated that, compared with Australian‐born women, East African maternal region of birth was associated with increased risk of perinatal death and some adverse perinatal outcomes 14 . Other Australian studies found an association between maternal region of birth and risk of obstetric intervention during birth 15,16 . Finally, another team in Victoria reported that late preterm births to South Asian‐born women were less likely to be admitted to the nursery and had better respiratory outcomes than those born to Australian/New Zealand‐born women 17 …”
Section: Introductionmentioning
confidence: 99%
“…14 Other Australian studies found an association between maternal region of birth and risk of obstetric intervention during birth. 15,16 Finally, another team in Victoria reported that late preterm births to South Asian-born women were less likely to be admitted to the nursery and had better respiratory outcomes than those born to Australian/New Zealand-born women. 17 Although this research provides important context, to date no studies have explored the relation between maternal region of birth and a broader composite indicator of neonatal morbidity comprising multiple components such as cerebral or respiratory conditions, need for respiratory support or intravenous fluids.…”
Section: Introductionmentioning
confidence: 99%
“…53,54 In general, Asian women have a lower BMI and have neonates with lower birth weights and fewer LGA infants than Caucasian women. 55,56 In contrast to these two previous studies, the current study presents data for a larger sample of 64 diabetic women, and outcomes are reported for women with GDM only, rather than combining potentially confounding results from women with GDM and pre-existing diabetes. We report data for a range of maternal and foetal characteristics, and analysed kidney size by assessing left and right kidney dimensions and volumes, as well as total kidney volume and total volume adjusted for foetal size.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence to suggest that the higher rate of stillbirth at term in South Asian-born women is due to differences in pregnancy length and feto-placental maturation. South Asian women have, on average, a 1 week shorter duration of pregnancy (11), higher rates of fetal compromise in late pregnancy and during labour (16), and babies that are more functionally mature at preterm gestations (17). Re ecting these local insights, the maternity program at Monash Health sought to implement a simple change in clinical practice to reduce the rate of term stillbirth in South Asian women.…”
Section: Introductionmentioning
confidence: 99%